1987
DOI: 10.1002/pen.760270409
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane elastomers containing polybutadiene and aliphatic diols: Polymerization and structure

Abstract: The effect of aliphatic diols on the polymerization and network formation of polyurethane elastomers containing hydroxyl terminated polybutadiene and three different diisocyanates was studied. The polymerization/curing progress was followed by viscosity measurements, IR spectroscopy, swelling, extraction, and hardness measurements. The resulting networks were characterized by swelling experiments. The type of diisocyanate and the diol chain length were found to have significant effects on the reacting mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…By applying Beer-Lambert law to the IR spectrum of transparent liquid film prepared above, Figure 2 shows linear plots of absorbance of isocyanate group in IR region with time, indicating second order for the curing reaction, as had been reported by other workers (7) for urethane reaction between isocyanate and alcohol. From this we can infer the following rate equation:…”
Section: Resultssupporting
confidence: 69%
“…By applying Beer-Lambert law to the IR spectrum of transparent liquid film prepared above, Figure 2 shows linear plots of absorbance of isocyanate group in IR region with time, indicating second order for the curing reaction, as had been reported by other workers (7) for urethane reaction between isocyanate and alcohol. From this we can infer the following rate equation:…”
Section: Resultssupporting
confidence: 69%
“…These substances belong to the formal class of polyurethane (PU) elastomers, especially those that recently contain hydroxyl-terminated polybutadiene (HTPB) (12)(13)(14). The HTPBbased polyurethane elastomers are superior to the common polyester-and polyether-based elastomers because they possess properties of lower water permeability, better stability in a moist atmosphere, higher electrical insulation, and lower glass-transition temperature (Tg) (15)(16)(17).…”
Section: Propellant Compositionmentioning
confidence: 99%
“…Oligomeric hydroxy‐terminated polybutadienes (HTPB) can potentially be used as a polyol component in the synthesis of more hydrophobic polyurethanes . HTPBs are also commercially available products used in composite propellants, adhesives, sealants, high‐quality binders for rubber crumb, potting materials and in electrical isolation, and gas separation equipment . HTPB‐based PUs represent an intermediate case with respect to polarity between rubber and usual PU elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the choice of the chain extender was mapped too. Previous investigations report on a zigzag pattern of for example decreasing and increasing tensile strength in case of elastomers based on aromatic diisocyanates. It has been observed that the mechanical properties are influenced by the number of carbon atoms in the chain extender .…”
Section: Introductionmentioning
confidence: 99%